2017
DOI: 10.1515/acph-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies and anticancer activity of curcumin-loaded nanostructured lipid carriers

Abstract: Pharmacokinetic studies and anticancer activity of curcumin-loaded nanostructured lipid carriersIn order to investigate the potential of nanostructured lipid carriers for efficient and targeted delivery of curcumin, the pharmacokinetic parameters of curcumin-loaded nanostructured lipid carriers (Cur-NLC) were evaluated in rats after a single intraperitoneal dose of Cur-NLC. In addition, the anticancer activity of Cur-NLC against human lung adenocarcinoma A549 cells was verified by a cellular uptake study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Curcumin, which is one of the traditional Chinese herbal formulations, exerts significant anticancer effects in many kinds of cancers. The increasing formulation of optimizations and analogues of curcumin are discovered [ 19 , 20 , 21 ]. T59 is a new formulation of optimized curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, which is one of the traditional Chinese herbal formulations, exerts significant anticancer effects in many kinds of cancers. The increasing formulation of optimizations and analogues of curcumin are discovered [ 19 , 20 , 21 ]. T59 is a new formulation of optimized curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a later study Chang and Chen 2 developed a curcuminoid nanoemulsion composed of curcuminoid extract, Tween 80 and water and studied its inhibition effect on lung cancer cells A549 and H460 growth, the IC 50 was shown to be 3.9 and 2.9 ppm, respectively, with the cell cycle being arrested at G2/M phase for subsequent activation of proapoptotic proteins such as caspase-3, leading to cell apoptosis. More recently, Wang et al 16 reported a higher antilung cancer activity towards A549 cells by curcumin-loaded nanostructured lipid carriers prepared by fast emulsication and low-temperature solidication, with an IC 50 value of 5.66 mg L À1 which was lower than for free curcumin (9.81 mg L À1 ). In addition, several comprehensive reviews on anticancer activity of curcumin and their analogues have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The total body clearance (Cl) value of Cur-NPs (4054.74±302.59 mL/h/kg) was much lower than in the Cur-DMSO group (28480.93±703.89 mL/h/kg), which is consistent with plasma concentration change tendency. Pharmacokinetic analysis showed that the relative bioavailability (F%)44 of Cur-NPs was 413.91%.…”
Section: Resultsmentioning
confidence: 99%